Posttraumatic Stress Disorder Specific to the COVID-19 Pandemic: Risk and Protective Factors among University Students - Feiler, Tatum I (East Carolina University, 2021)
There is minimal research examining the effects of pandemics on college student mental health, so it remains unclear if there are risk and protective factors unique to this group that influence the development of post-traumatic stress disorder (PTSD). The objectives of this study are to: 1) determine the rate of positive screens for PTSD specific to the coronavirus pandemic in an undergraduate and graduate student sample; 2) determine which risk factors identified in previous research (e.g., higher actual or perceived risk of exposure, compliance with measures to prevent infections) are associated with an increased rate of PTSD; and 3) determine which protective factors identified in previous research (e.g., social support, access to counseling services) are associated with a decreased rate of PTSD. After obtaining IRB approval, undergraduate and graduate students at a large southeastern public university were recruited to participate in this online survey study during the 2020 fall semester. In order to meet our target sample size of 400 students, participants were recruited from a random sample provided by the university, the university Psychology Department Introductory Psychology participant pool, and emails to student organizations, undergraduate and graduate advisors. Upon completion of the survey, participants in Introductory Psychology courses were provided research credit and all other participants were entered into a gift card raffle. PTSD was assessed with the PTSD Checklist for the DSM-5. Risk and protective factors were assessed using the Stressful Life Events Screening Questionnaire, Brief Coping Orientations to Problems Experienced Scale, Patient Health Questionnaire 8, Generalized Anxiety Disorder 7 Scale, MOS Social Support Survey, UCLA Loneliness Scale, Lubben Social Network Scale, Brief Assessment of Family Functioning Scale, and items our team developed and sampled from other epidemic studies. The data were analyzed using SPSS Version 27 during the 2021 spring semester. Twenty-one percent of participants screened positive for PTSD specific to the COVID-19 pandemic using the PTSD Checklist for the DSM-5 (PCL-5). Seven percent of participants screened positive for COVID-19 specific PTSD using the PTSD Checklist for the DSM-5 (PCL-5) and met the DSM-5 criterion A for trauma exposure (i.e., actual or threatened death, serious injury, or sexual violence). A series of logistic regressions were conducted using the more conservative PTSD classification as the criterion variable, risk and protective factors as predictor variables, and using a Bonferroni adjusted p-value of .0016 to determine significance. Significant risk factors for PTSD during the COVID-19 pandemic were: a poor self-rating of health, prior trauma, poor family functioning, COVID-19 anxiety, depression symptoms, and the use of maladaptive coping strategies. Significant protective factors were social connection to family and friends and the use of adaptive coping strategies. This study’s findings can help inform universities and broader society about the mental health needs of university students during a pandemic and provide guidance into developing university programs, policies, and informed interventions to meet student needs.
Keywords: Posttraumatic Stress Disorder; COVID-19